Should tax policy favor high- or low-productivity firms? - Dominika Langenmayr; Andreas Haufler; Christian J. Bauer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2012)
Heterogeneous firm productivity seems to provide an argument for governments to pursue `pick-the-winner' strategies by subsidizing highly productive firms more, or taxing them less, than their less productive counterparts. We appraise this argument by studying the optimal choice of effective tax rates in an oligopolistic industry with heterogeneous firms. We show that the optimal structure of tax differentiation depends critically on the feasible level of corporate profit taxes, which in turn depends on the degree of international tax competition. When tax competition is moderate and profit taxes are high, favoring high-productivity firms is indeed the optimal policy. When tax competition is aggressive and profit taxes are low, however, the optimal tax policy is reversed and low-productivity firms are tax-favored.
Keywords: H25; H87; F15; 330; business taxation; firm heterogeneity; tax competition; Unternehmensbesteuerung; Ertragsteuer; Steuerbegünstigung; Unternehmen; Produktivität; Steuerwettbewerb; Optimale Besteuerung; Theorie